Graft copolymerization of methyl methacrylate onto oil palm empty fruit bunch fiber using H2O2/Fe2+ as an initiator - Ibrahim, Nor Azowa; Wan Md Zin, Wan Yunus; Abu-Ilaiwi, Faraj A.; Ab Rahman, Mohd Zaki; Ahmad, Mansor; M. Dahlan, Khairul Zaman (Wiley, 2003)
Graft copolymerization of methyl methacrylate (MMA) onto oil palm empty fruit bunch fiber (OPEFB) was successfully carried out in aqueous medium using hydrogen peroxide as an initiator. Results from the investigation of the optimum conditions for grafting are presented. Maximum percentage of grafting was achieved when the amount of initiator, cocatalyst, and nitric acid were 5.877 × 10-3 mol, 2.63 × 10-4 mol, and 3.24 × 10-3 mol, respectively. The optimum reaction temperature was 50°C and the reaction period was 120 min. The highest percentage of grafting and grafting efficiency were 220 and 47%, respectively, under optimum conditions. The grafted copolymer was characterized by FTIR spectroscopy and scanning electron microscopy. The presence of a band at 1730 cm-1 provides strong evidence of grafting.